Level of knowledge of organ donation and sociodemographic factors in medical students: a cross-sectional study - Albújar Castillo, Mariana (2022)
Objective: To determine the level of knowledge of organ donation (LKD) in tenth-semester Human Medicine students and its relationship with some sociodemographic variables.Materials and methods: A cross-sectional survey study conducted with 121 students from a Peruvian university. A questionnaire consisting of five sociodemographic characteristics and 10 questions about LKD was used. Besides the descriptive analysis, a chi-square test was used to compare LKD with the sociodemographic characteristics, considering a significant relationshipwhen the p value was less than 0.05.Results: The average age of the students was 23 ± 2.3 years, 51.2 % were males, 78.5 % practiced a religion, 83.5 %acquired their knowledge in an academic environment and 24.8 % had a family member or close friend who neededan organ transplant. Forty-seven percent (47 %), 42 % and 11 % of the students had a high, medium and low LKD,respectively. According to the bivariate analysis, there was no relationship between LKD and the age group of thestudents (p = 0.696), their sex (p = 0.794), the origin of their knowledge (p = 0.734) or having an acquaintancewho needed an organ donation (p = 0.269); however, it was related (p = 0.008; 95% CI 0.008 – 0.011) to practicinga religion.Conclusions: Most tenth-semester Human Medicine students had a high LKD, which was related to practicing a religion.